"The Vatican was for us like a mountain": Reassessing the Vatican’s Role in Jewish Relief and Rescue during the Holocaust. Settled Questions and New Directions in Research. - Ventresca, Robert A. (Studies in Christian-Jewish Relations, 2014)
No abstract is available.